Kulturminnelovens terskel: Klassifisering av kontekstløse ringformede spenner fra middelalder og nyere tid - Mats Skare (Viking, 2023)
The annular brooch makes up one of the most prevalent brooch types from the medieval period in Europe. Moreover, its use and production in Norway last well into the modern period. This has resulted in a quandary. The Norwegian Cultural Heritage Act labels all artefacts older than AD 1537 as state property (1650 for coins). With a few exceptions, everything younger may be acquired by the finder. But how is this to be decided for stray finds of annular brooches? How can these be dated?